2016
DOI: 10.1038/onc.2016.149
|View full text |Cite
|
Sign up to set email alerts
|

GPC5, a novel epigenetically silenced tumor suppressor, inhibits tumor growth by suppressing Wnt/β-catenin signaling in lung adenocarcinoma

Abstract: Glypican-5 (GPC5) is a member of the heparin sulfate proteoglycans. Previous studies of GPC5 in lung tumorigenesis showed conflicting results. In this study, we confirmed that GPC5 was downregulated in lung adenocarcinoma tissues compared with adjacent normal lung tissues. The low expression of GPC5 was significantly associated with poor outcome in lung adenocarcinoma. To understand the biological mechanism of the downregulation, we examined the promoter methylation status of GPC5 gene. We found that GPC5 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…Similar evidence has also been obtained in cerebellar granule cell precursors [6] and salivary adenoid carcinoma [7]. Conversely, overexpression of GPC5 inhibits prostate [8] and lung cancer cell proliferation [9]. In non-small cell lung cancer, some reports have suggested that GPC5 is a tumor promoter [10], whereas others insist that it is a tumor suppressor [11,12].…”
Section: Introductionsupporting
confidence: 67%
“…Similar evidence has also been obtained in cerebellar granule cell precursors [6] and salivary adenoid carcinoma [7]. Conversely, overexpression of GPC5 inhibits prostate [8] and lung cancer cell proliferation [9]. In non-small cell lung cancer, some reports have suggested that GPC5 is a tumor promoter [10], whereas others insist that it is a tumor suppressor [11,12].…”
Section: Introductionsupporting
confidence: 67%
“…Cell counting kit-8 (CCK-8) assay, colony formation assay, cell migration and invasion assays were described previously (Yuan et al, 2016).…”
Section: Cell Counting Kit-8 Assay Colony Formation Assay Cell Migrmentioning
confidence: 99%
“…Western blot (WB) was performed as described previously (Yuan et al, 2016). The antibodies used in this study were rabbit monoclonal antibody to EPAS1 (HIF-2-alpha; 1 : 1000; Abcam Inc., Cambridge, MA, USA), rabbit monoclonal antibody to E2F6 (1 : 1000; Abcam) and rabbit polyclonal antibody to b-actin (1 : 5000; Abcam).…”
Section: Western Blot and Immunohistochemistrymentioning
confidence: 99%
“…Cell Counting Kit-8 (CCK-8) assay, colony formation assay, cell migration and invasion assays were performed as described in Yuan et al, 2016. [17] Animal experiments in vivo For in vivo tumorigenicity, ten male BALB/c-nude mice (4-week-old) were randomly divided into two groups, with ve mice in each group. Stable transfected A549 cells (5.0 × 10 6 ) were injected subcutaneously into the left anks of the nude mice (100 ul per mouse).…”
Section: Cell Counting Kit-8 Assay Colony Formation Assay Cell Migrmentioning
confidence: 99%
“…Western blot (WB) was performed as described previously (Yuan et al, 2016) [17]. The antibodies used in this study were rabbit monoclonal to MYC (Abcam Inc., Cambridge, MA) (1:2000; Abcam (ab32072)), rabbit monoclonal to ELAVL1 (1:5000; Abcam (ab200342)), rabbit monoclonal to AGO2 (1:2000; Abcam (ab186733)), rabbit monoclonal to BCL2L11 (1:2000; Abcam (ab32158)), rabbit monoclonal to Histone H3 (1:5000; Abcam (ab176842)), rabbit polyclonal to β-actin (1:5000; Abcam (ab8227)).…”
Section: Western Blotmentioning
confidence: 99%